Covid-19 and lack of linked datasets for care homes. (24th June 2020) - Hanratty, Barbara; Burton, Jennifer Kirsty; Goodman, Claire; Gordon, Adam L; Spilsbury, Karen
Abstract : The pandemic has shed harsh light on the need for a live minimum dataset